Prevalence on the complement in offering food to newborns - Josilene Maria Ferreira Pinheiro; Taiana Brito Menêzes Flor; Amanda Michelly Braga da Mata; Vanessa Cristina da Costa Pires; Luana Isabelly Carneiro de Oliveira; Wanessa Pinheiro de Macedo Barbosa; Fábia Barbosa de Andrade (Instituto Materno Infantil de Pernambuco, 2021)
Abstract Objectives: to identify the prevalence and determining factors of the complements in offering food to newborns. Methods: across-sectional study nested to a cohort study that assessed newborn care in four public maternity hospitals in Natal/Brazil. Sample was composed by 415 mothers and full-term newborns, with appropriate weight for gestational age and Apgar scores in 1st and 5th minutes ≥ 7. In order to analyze the determining factors, we used Poisson's regression. Results: from 415 newborns, 51.3% received feeding complements (57.6% in the first hour of life), of which 92% was infant formula. Only 50.7% of those complement in offering food were prescribed by physicians. Colostrum deficiency was the main reason to be indicated (33.8%). Maternal age ≤ 20 years old (PR=0.64; CI95%=0.47-0.86) and between 2030 years old (PR=0.70; CI95%=0.57-0.87)comparing to women older than 30 were shown as protective factors, while being primiparous (PR=1.37; CI95%=1.11-1.60) and had cesarean section (PR=1.2; CI95%=1.00-1.45) as risk factors. Conclusion: maternal characteristics are associated with the complement in offering food to the newborn in the first hours of life. The high prevalence shows the need for interventions that minimize the inadequate offer of infant formula and promote exclusive breastfeeding before hospital discharge.